То, что сильнее: [рассказы] / Мария Метлицкая - Метлицкая Мария (За чужими окнами, 2015)
Экземпляры: Селеговская биб-ка (20181219) / Инвентарный номер: 45393 / Цена: 118 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: М 54 / ГРНТИ: 17.82.32 / ББК: 84(2Рос=Рус)6